Applicability of two violence risk assessment tools in a psychiatric prison hospital population. (7th July 2020) - Krebs, Julia; Negatsch, Vincent; Berg, Christine; Aigner, Annette; Opitz‐Welke, Annette; Seidel, Peter; Konrad, Norbert; Voulgaris, Alexander
Abstract : The risk of violent behavior is known to be higher for patients who suffer from a severe mental disorder. However, specific prediction tools for clinical work in prison psychiatry are lacking. In this single‐center study, two violence risk assessment tools (Forensic Psychiatry and Violence Tool, "FoVOx, " and Mental Illness and Violence Tool, "OxMIV") were applied to a prison hospital population with a primary psychotic or bipolar disorder and subsequently compared. The required information on all items of both tools was obtained retrospectively for a total of 339 patients by evaluation of available patient files. We obtained the median and inter‐quartile range for both FoVOx and OxMIV, and their rank correlation coefficient along with 95% confidence intervals (CIs)—for the full cohort, as well as for cohort subgroups. The two risk assessment tools were strongly positively correlated (Spearman correlation = 0.83; 95% CI = 0.80–0.86). Such a high correlation was independent of nationality, country of origin, type of detention, schizophrenia‐spectrum disorder, previous violent crime and alcohol use disorder, where correlations were above 0.8. A lower correlation was seen with patients who were 30 years old or more, married, with affective disorder and with self‐harm behavior, and also in patients without aggressive behavior and without drug use disorder. Both risk assessment tools are applicable as an adjunct to clinical decision making in prison psychiatry.